The Phenomenon of Emergency in Socio-Economic and Strategic Aspects - S. A. Grinev (Управленческое консультирование, 2023)
The article is devoted to the analysis of the structure and content of socio-economic crises as manifestations of emergencies and corresponding periods. With the help of general scientific and special methods, including comparative, the author reveals the evolution of crisis phenomena in the economy in relation to emergency periods, essentially reflecting the phenomenon of emergency. The historical analysis of economic crises is illustrated by the graphs of the impact of crises on basic economic indicators compiled by the author. The author’s definition of the concept of “emergency period” is given with the specification of the phenomena of its components (situation, situation, circumstance, incident). On the basis of V.L. Kvint’s strategic methodology, the necessity of strategizing the emergency period from the point of view of prevention, overcoming and getting out of it is substantiated. At the same time, the author believes that economic crises from their inception to their peak are essentially extraordinary periods that require appropriate strategizing according to the phases of the economic cycle: strategies for crisis prevention, prevention or mitigation of depression, as well as ensuring the revival of the economy with an exit from a particular emergency period.